Privatization of public order in the Iberian world, late 19th-early 20th century - Castillo Cañiz, Assumpta (Historia y Política, 2025)
ms of security in Spain and Portugal between the late nineteenth century and the years leading up to the Great War. Drawing on the study of three medium-sized cities in the rural periphery of both countries and on legal, press, and archival sources, it analyses the activities of private security actors and forces, as well as the private use of public force and its potential privatization. The main objectives are, first, to assess whether these groups could have been part of a hybrid public-private model of police deployment and public order management, which played a significant role in extending the state’s repressive capacity and consolidating its administrative apparatus. Second, to evaluate whether this mixed model also contributed substantially to covering peripheral rural areas.